The Latin renovatio of Byzantium - Tricht, Filip van (My University, 2011)
In 1204 the army of the Fourth Crusade sacked the great city of Constantinople. Through a comprehensive rereading of better and lesser-known sources this book offers an alternative perspective on this event, arguing that the Latin rulers did not abolish, but very consciously wanted to continue the Eastern Empire
The Empire of Constantinople (1204-1228)
By Filip Van Tricht ; translated by Peter Longbottom. - Leiden ; Boston : Brill, 2011. - xii, 535 p. : maps ; 25 cm.- Includes bibliographical references (p. [483]-519) and index
Contents: Prologue-The constitutional treaties of 1204-1205 : the Latin restructuring of Byzantium-The imperial ideology-The imperial quarter-Imperial authority within the empire in its entirety-The central elite-Religion, church, and empire-The Byzantine space-The Latin Orient
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ՖԲ Library of Byzantine Studies կայքից
https://mamlikshistory.blogspot.com/2023/04/download-pdf-latin-renovatio-of.html
Keywords: Crusades-Fourth, 1202-1204; Imperialism-Social aspects-Byzantine Empire-History; Social change-Byzantine Empire-History; Latin Empire, 1204-1261; Istanbul (Turkey)-History-Siege, 1203-1204; Istanbul (Turkey)-History-To 1453; Istanbul (Turkey)-Politics and government; Istanbul (Turkey)-Social conditions; Byzantine Empire-History-1081-1453; Byzantine Empire-Politics and government